Functional Imaging of the Human Brainstem during Somatosensory Input and Autonomic Output - Henderson, Luke A.; Macefield, Vaughan G. (Frontiers in Human Neuroscience, 2013)
Over the past half a century, many experimental animal investigations have explored the role of various brainstem regions in a variety of conditions. Despite the accumulation of a considerable body of knowledge in primarily anaesthetized preparations, relatively few investigations have explored brainstem function in awake humans. It is important that human brainstem function is explored given that many neurological conditions, from obstructive sleep apnea, chronic pain and hypertension, likely involve significant changes in the processing of information within the brainstem. Recent advances in the collection and processing of magnetic resonance images, has resulted in the possibility of exploring brainstem activity changes in awake healthy individuals and in those with various clinical conditions. We and others have begun to explore changes in brainstem activity in humans during a number of challenges, including during cutaneous and muscle pain, as well as during challenges that evoke increases in sympathetic activity. More recently we have successfully recorded sympathetic nerve activity concurrently with fMRI of the brainstem, which will allow us, for the first time to explore brainstem sites directly responsible for conditions such as hypertension. Since many conditions will involve changes in brainstem function and structure, defining brainstem changes will likely result in a greater ability to develop more effective treatment regimes.